Roles for community health workers in diabetes prevention and management in low- and middle-income countries - Babagoli, Masih A; Nieto-Martínez, Ramfis; González-Rivas, Juan P; Sivaramakrishnan, Kavita; Mechanick, Jeffrey I (Cadernos de saude publica, 2021)
Diabetes prevalence is increasing worldwide, especially in low- and middle-income countries (LMIC), posing the need for improved detection and management strategies. Chronic disease models and lifestyle medicine provide structures for action. Community health workers (CHWs) can significantly contribute to chronic disease care if they are trained and integrated into low-resource health systems. Although most current CHWs worldwide are performing maternal/child health and infectious disease-related tasks, other programs involving CHWs for noncommunicable disease prevention and management are increasing. In this article, we discuss the advantages, challenges, and questions regarding possible roles assigned to CHWs in the prevention and management of diabetes. These roles include performing simple screening tests, implementing lifestyle/behavioral interventions, and connecting patients with alternatives to biomedicine. Specifically, CHWs can aid diabetes epidemiological surveillance by conducting risk score-based screening or capillary glucose testing, and they can facilitate diabetes self-management by delivering interventions described in the transcultural diabetes nutrition algorithm. Furthermore, while this role has not formally been assigned, CHWs can leverage their intimate knowledge of local practices to provide decision-making support to patients in environments with pluralistic health systems. Ethnocultural differences in CHW functions and transcultural adaptations of their roles in diabetes care should also be considered. In summary, CHWs can improve diabetes care by screening high-risk individuals and implementing lifestyle interventions, especially in LMIC.
Keywords: rozvojové země; zdravotní pomocníci v komunitě; chudoba; Community Health Workers; Diabetes Mellitus; Brazil; poskytování zdravotní péče; Humans; Developing Countries; Poverty; Brazílie; diabetes mellitus; dítě; lidé; Delivery of Health Care; Child